2016
DOI: 10.1016/j.ijcci.2016.10.001
|View full text |Cite
|
Sign up to set email alerts
|

Designing an educational music game: What if children were calling the tune?

Abstract: This paper presents the design process of an educational digital music game that offers primary school children a first experience with music education. A fourphased Participatory Design (PD) trajectory was followed: exploratory interviews, Proxy Technology Assessment using the MemoLine instrument, codesign sessions and evaluation of the first demonstrator. This paper describes how PD principles can be used in obtaining design requirements for educational digital music games for children. The results highlight… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
25
0

Year Published

2017
2017
2025
2025

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(25 citation statements)
references
References 25 publications
0
25
0
Order By: Relevance
“…Alternatively, some researchers have approached values as an open question -they are to be revealed through empirical inquiry without a predefined value set (e.g. [25,26,70,[73][74][75]). The latter type of studies emphasize the dynamic, evolving and context dependent nature of values (see e.g.…”
Section: Values and Value-driven Design Approachesmentioning
confidence: 99%
See 1 more Smart Citation
“…Alternatively, some researchers have approached values as an open question -they are to be revealed through empirical inquiry without a predefined value set (e.g. [25,26,70,[73][74][75]). The latter type of studies emphasize the dynamic, evolving and context dependent nature of values (see e.g.…”
Section: Values and Value-driven Design Approachesmentioning
confidence: 99%
“…There already is a growing interest in the topic of children's online safety in CCI and Human-Computer Interaction (HCI) research, papers reporting for example parental [19,20] and societal [12,21] concerns, children's risky actions [1] as well as means by which online risks could be mitigated [22][23][24] and solutions for preventing certain kind of online behavior [22,25]. There are also numerous examples of participative design with children addressing their education, papers reporting collaboration with children for example in the design [26][27][28][29] and evaluation [30] of educational games, and evaluating children's engagement with these games [31]. Collaboration is seen to improve the quality of the solutions as well as giving a democratic possibility for people who are affected by the decisions to influence design [32].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, rhythm games are suggested to develop skills on how to use notes [4]. Also, it is reported that gamers of this genre have shown high level rhythm recognition skills on certain musical instrument through playing [5,6]. The educational effect of this genre, however, is not clearly shown by a systematic review [7] but its intrinsic value on potential creativity learning is encouraged [8,9].…”
Section: Introductionmentioning
confidence: 99%
“…Schools need to develop practical ways to meet these new demands over coming years. One starting point is with children making or designing educational games which is now generally accepted as a valid learning activity for 21st century skills [30,32] and has been explored in three different but overlapping fields of research: codesign with children [16,38,39] , constructionist game making [11,17,31,34,56] and serious games [30] . Each field has independently developed a number of methodologies [13,33,55] , performed a multitude of case studies and reached conclusions about a range of subjects from group dynamics [52] and adult involvement [58] to learning outcomes [30,44,58] and methods of evaluation [14,53] .…”
Section: Introductionmentioning
confidence: 99%